"As If Heaven Was Warning": Omens and Interpretations in Shen Yue’s Song shu 宋書 - Kou, Lu (JAOS, 2025)
Propagating omens constituted a crucial strategy to bolster a dynasty’s claim of political legitimacy in early medieval China. While it was believed that Heaven indicated its approbation or reproach of the ruler through omens, in the fifth and sixth centuries, when rival states fought with weapons and words, how to interpret signs and understand Heaven’s will became a contentious issue. A "semiotic warfare" was waged, where the Northern Wei and its southern enemies, Song, Qi, and Liang, competed to define and contest the rules of reading and the scope of their semiotic practices. This aticle examines omen reading in Shen Yue’s (441-513) treatises on "Heavenly Patterns" ("Tianwen"), the "Five Phases" ("Wuxing"), and "Auspicious Omens" ("Furui") in the Song shu. The three treatises show a drastic shift in strategies of interpretation: from a contextualized mode of sense making in "Tianwen" and "Wuxing" to a decontextualized reading in "Furui." Analyzing these treatises against the background of semiotic competition, this article argues that "Furui zhi" represents Shen Yue’s attempt to redress the interpretive multiplicities in the other two treatises and to prevail in the discursive wars over legitimacy by forestalling verbal maneuvers of contexts and eliminating interpretive flexibility.